Anger, mercy, revenge - Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D (Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D. Works. 2010., 2010)
Lucius Annaeus Seneca (4 BCE-65 CE) was a Roman Stoic philosopher, dramatist, statesman, and advisor to the emperor Nero, all during the Silver Age of Latin literature. The Complete Works of Lucius Annaeus Seneca is a fresh and compelling series of new English-language translations of his works in eight accessible volumes. Edited by world-renowned classicists Elizabeth Asmis, Shadi Bartsch, and Martha C. Nussbaum, this engaging collection restores Seneca--whose works have been highly praised by modern authors from Desiderius Erasmus to Ralph Waldo Emerson--to his rightful place among the classic.